Revisiting Traditional Communication in Indonesia: Why do Self-Immunity Rituals of Pelauw Indigenous Community, Moluccas - M. Ridwan; Sulaeman, Sulaeman (Technium Social Sciences Journal, 2020)
Culturally, self-immunity is one of the diversity of traditional communication in Indonesia. Self-immunity, the ritual has an integrated interaction of the relationship of Islamic teachings with traditional values. The self-immunity communication, beginning with salvation prayer is integrated with the medium. Such as the use of machetes, swords, drums, tambourines, to forms of self-courage testing with the power given from the ancestors to hurt limbs. The research is focused on expressing the motives and symbols exploration and meanings of self-immunity ritual communication. Through a phenomenological communication approach and a qualitative interpretive paradigm with data collection techniques on interviews supported by observations based on the symbolic communication perspective. The motives experienced Indigenous community due to the soul calling, willingness to preserve indigenous and ancestral culture, and self-appreciation seeking that has value and beliefs affects the Indigenous community life. The meaning as a plea to Allah, respect to ancestors, and the spirit of struggle based on the self-immunity ritual communication procession, starting with clan house, sacred tombs, self-cleansing, self-courage testing, and fabric on the neck.